Technology acceptance model (TAM) on the drivers iPad used by university academicians: a conceptual model - Lee Choy Ying; Nur Balqishanis Binti Zainal Abidin (Universitas Internasional Batam, 2023)
This research paper suggests a conceptual model for the academic staff adoption of iPad at university. With the enhancement of technology, knowledge can be developed more efficiently and effectively for the Teaching and Learning (T&L) process. iPad has become an important technology tool in the advancement of education, particularly in classroom instruction. Therefore, the purpose of this study is to investigate the dimensions of the drivers of iPad used by university academicians based on the technology acceptance model (TAM). The methodology used for this study, was to extract the critical factors from TAM. The five critical factors that supported the TAM theory are perceived ease of use (PEOU), perceived usefulness (PU), behavioral intention (BI), attitude (ATT) and frequency of actual use of iPad (AU). All these critical factors determined and validated by supported preceding articles and represent as the proposed dimensions for the conceptual model. Next, the hypotheses developed for each association among the critical factors. The findings drawn from the developed hypotheses generally lead to the development of a conceptual model. The limitation of this study is just to provide the conceptual notion; thus, this model could extend to the empirical analysis in the future.